Prevalência e fatores associados à ocorrência de sífilis em adolescentes de Feira de Santana/Bahia, 2003-2012 - Monteiro, Milena de Oliveira Pérsico (2014)
Syphilis is a sexually transmitted disease that still represents a serious public health problem. In Brazil, it is estimated a prevalence of syphilis of 1.10%, for different age groups, and the infected women have an earlier age than men and in pregnant women, the prevalence ranges from 1.40% to 2.40 %. The sexual behavior of adolescents is presented as a priority for the implementation of specific policies, on multiple factors and vulnerabilities associated with the occurrence of this condition. Objective: To investigate the factors associated with syphilis in the range 11-18 years, of both sexes and pregnant women registered in the Testing and Counseling Center/CTA Municipal Reference Center / CRM Feira de Santana, Bahia / Brazil. Methodology: A cross-sectional study, with the CTA Information System data, from 2003 to 2012. We evaluated 3,482 medical records and conducted descriptive analyzes of sociodemographic, clinical and behavioral characteristics, calculating p <0.05. Results: 1.95% (13) for males, 1.18% (14) for females and 0.18% among pregnant adolescents. The reasons for seeking the service and the factors associated with syphilis were different for men, women and pregnant teenagers. In the group of non-pregnant women, coinfection was observed HIV-syphilis, and association between use of drugs and alcohol with the outcome. Regardless of HIV status, for both groups, the low and sex prevalence of condom use were shown as the main sources of exposure. Conclusions: in non-pregnant women was an association between syphilis, drug / alcohol and HIV coinfection. These findings point to the need for measures to prevent syphilis infection, especially in vulnerable situations, such as drug use and HIV.